Sejarah Perkembangan Bimbingan Konseling (BK) - Hidayani Syam; Amelia Maharani; Rafita Gusti Putri; Agus Salim (Kampus Akademik Publiser, 2025)
Guidance & counseling (BK) is a field of science that is serious about helping individuals with self-development, problem-solving, & decision-making.Its development has taken place from the antique era to the formal discipline known today.In antique Greece, figures such as Socrates & Plato emphasized the importance of conversation & reflection on self-development.Later, in medieval times, the concept of guidance existed through the work of religion, especially in putting moral direction.The most recent era was marked by the emergence of career guidance in the United States in the early 20th century, pioneered by Frank Parsons, known as the